1995
DOI: 10.1007/bf02207674
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen months' follow-up of intensive inpatient physiotherapy and exercise in ankylosing spondylitis

Abstract: Long-term effects of three or four-week inpatient physiotherapy and exercise courses were studied in 141 adult patients with ankylosing spondylitis (AS). Eight cervical and thoracolumbar range of motion (ROM) measurements and straight leg raise test, vital capacity (VC) and fitness index were measured at the beginning and end of an intensive course and 15 months later. All nine mobility measurements, vital capacity and fitness index were significantly improved after the course. Fifteen months later only chest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
8

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 20 publications
0
18
0
8
Order By: Relevance
“…__Physical therapy applied individually or in groups has general and specific beneficial effects for patients suffering from AS [28,29,30]. Several studies reported improvement in the wall-to-occiput distance, finger-to-floor distance, chest expansion, Schober Index, and pulmonary function after a couple of weeks of intensive physiotherapy [1,14,31,32]. __In study II, which was a prospective but nonrandomized self-controlled study, we investigated functional and physical parameters with respect to the above mentioned structural-functional changes in AS patients currently receiving anti-TNF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…__Physical therapy applied individually or in groups has general and specific beneficial effects for patients suffering from AS [28,29,30]. Several studies reported improvement in the wall-to-occiput distance, finger-to-floor distance, chest expansion, Schober Index, and pulmonary function after a couple of weeks of intensive physiotherapy [1,14,31,32]. __In study II, which was a prospective but nonrandomized self-controlled study, we investigated functional and physical parameters with respect to the above mentioned structural-functional changes in AS patients currently receiving anti-TNF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Vesovic-Potic et al [25] reported significant correlation between disease duration, symptoms duration and BASFI. The efficacy of various physiotherapy programs has been assessed by several groups [12,14,15,[26][27][28] concluding that exercise programs are important and useful part of the complex therapy of ASDagfinrud et al [14] recently reviewed the available body of evidence on the efficacy of physiotherapy interventions in AS. This meta-analysis suggests that an individual homebased or supervised exercise program is better than having no intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that by intensive rehabilitation courses it is possible to prevent deterioration of spinal function, however fitness in AS patients irrespective of disease duration [12]. The efficacy of intensive inpatient physiotherapy has been reported by changes in subjective and functional parameters, from which OWD, CE and FFD showed the greatest improvement [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three to four weeks of intensive, inpatient therapy was found to improve spine range of motion, vital capacity, and a general fitness index, both at the end of the treatment program and at a 15month follow-up visit (20). Another study determined that patient education and a home exercise p r e gram over a 4month period increased back flexibility as measured by fingertip to floor distance, but not by Schober's test (14).…”
Section: Discussionmentioning
confidence: 99%